Methoxypyrazine concentrations in the grape bunch rachis of Vitis vinifera L. Cv Shiraz: Influence of rootstock, region and light. (15th May 2023) - Sanders, Ross D.; Boss, Paul K.; Capone, Dimitra L.; Kidman, Catherine M.; Maffei, Sue; Jeffery, David W.
Graphical abstract: Highlights: Methoxypyrazines are not present in Shiraz grape but are in bunch stem (rachis) Rootstock can influence methoxypyrazine (MP) concentrations in the rachis of Shiraz. Vine vigour associated with rootstock had positive correlations with MPs in rachis. Exclusion of sunlight from bunches increased MP concentrations in rachis. Terroir (related to climate, soil, vine management) also influences MPs in rachis. Abstract: Vitis vinifera L. cv Shiraz appears unable to synthesise 3-alkyl-2-methoxypyrazines (MPs) in the berry, but can still produce significant concentrations in rachis. MPs are readily extracted from rachis during fermentation, producing Shiraz wines with uncharacteristic "green" flavours. Recently, rootstocks were shown to significantly alter MP concentrations in Cabernet Sauvignon rachis compared to own-rooted varieties, but whether Shiraz followed a similar trend required investigation. This study considered the effect of thirteen rootstocks on the concentrations of 3-isobutyl-2-methoxypyrazine (IBMP), 3-isopropyl-2-methoxypyrazine (IPMP), and 3- sec -butyl-2-methoxypyrazine (SBMP) in the rachis of Shiraz bunches sampled during multiple vintages across several Australian growing regions. Although IBMP was the most abundant, all measured MP concentrations were significantly affected by vintage, rootstock, and region. In addition, vine vigour showed positive correlations with IBMP, which were attributed to changes in canopy coverage impacting rachis light exposure. This hypothesis was explored with light exclusion trials, which significantly increased rachis IBMP concentrations.